Current status of food safety hazards and health risks connected with aquatic food products from Southeast Asian region - Peiru Gao; Nor Qhairul Izzreen Mohd Noor; Sharifudin Md. Shaarani (2020)
Food safety issues associated with aquatic food products become more important with the increasing consumption and followed by its ongoing challenges. The objective of this paper is to review the food safety hazards and health risks related to aquatic food products for the Southeast Asian region. These hazards can be categorized as microplastics (MPs) hazard, biological hazards (pathogenic bacteria, biogenic amines, viruses, parasites), and chemical hazards (antimicrobial, formaldehyde, heavy metal). In different Southeast Asian countries, the potential health risks of aquatic food products brought by food hazards to consumers were at different intensity and classes. Among all these hazards, pathogenic bacteria, antimicrobials, and heavy metal were a particular concern in the Southeast Asian region. With environmental changes, evolving consumption patterns, and the globalization of trade, new food safety challenges are created, which put forward higher requirements on food technologies, food safety regulations, and international cooperation.